Escape from Mogadishu [videorecording (DVD)] - Yu, Sŭng-wan, 1973-; Kim, Yun-sŏk, 1968-; Cho, In-sŏng, 1981-; Heo, Jun-ho, 1964-; Koo, Kyo-hwan, 1982-; Kim, So-jin, 1979-; Chŏng, Man-sik, 1974-; Kim, Jae-hwa, 1980-; Park, Kyung-hye, 1993- (Well Go USA Entertainment, 2022)
Based on a true story: as civil war rages in Mogadishu, rival North and South Korean diplomats are left trapped. With no aid from either government, their only shot at survival may require uniting with bitter adversaries to escape.